2019
DOI: 10.1002/sia.6625
|View full text |Cite
|
Sign up to set email alerts
|

Application of surface analysis in study on removal mechanism and abrasive selection during fused silica chemical mechanical polishing

Abstract: In this work, surface analysis technology is employed to investigate the removal mechanism and the selection of abrasive during fused silica chemical mechanical polishing (CMP). Morphology of abrasives is inspected by scanning electron microscope (SEM). The atomic force microscope (AFM) is used to determine the surface roughness (Rq) and undulating (PV) of the polished fused silica surface. The resultsshow that abrasive morphology has a tremendous influence on removal rate (MRR) and PV but has little effect on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…Several studies reported and described how it is possible to obtain SiO 2 nanoparticles (NPs) with different aspect ratios and textural properties, involving different types of porosities and high active surface areas [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. Furthermore, its chemical inertness and insulating features favor the exploitation of SiO 2 in a plethora of technological applications [ 28 , 29 , 30 , 31 , 32 , 33 ]. Among these, SiO 2 is widely applied in nanocomposite formulations (as filler) [ 34 , 35 , 36 ], industrial catalysis (as substrate) [ 37 , 38 , 39 ], wastewater remediation processes (as adsorbent) [ 40 , 41 ], as a building material component [ 42 , 43 ], and in different advanced biomedical applications (e.g., as a drug-carrier system) [ 44 , 45 , 46 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies reported and described how it is possible to obtain SiO 2 nanoparticles (NPs) with different aspect ratios and textural properties, involving different types of porosities and high active surface areas [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. Furthermore, its chemical inertness and insulating features favor the exploitation of SiO 2 in a plethora of technological applications [ 28 , 29 , 30 , 31 , 32 , 33 ]. Among these, SiO 2 is widely applied in nanocomposite formulations (as filler) [ 34 , 35 , 36 ], industrial catalysis (as substrate) [ 37 , 38 , 39 ], wastewater remediation processes (as adsorbent) [ 40 , 41 ], as a building material component [ 42 , 43 ], and in different advanced biomedical applications (e.g., as a drug-carrier system) [ 44 , 45 , 46 ].…”
Section: Introductionmentioning
confidence: 99%
“…Correspondingly, the chemical effects during the interaction between MR fluid and workpiece were considered. Jacobs reported that the aqueous based MR fluid showed significant higher MRR (two-magnitude enhancement) when compared with the non-aqueous MR fluid in MRF while finishing the fused silica (FS) [11], such phenomenon indicated the water can significantly enhance the MRR in FS finishing. The origin of the enhanced MRR can be summarized into two perspectives: (a) dissolution of the FS, then its hardness can be reduced to facilitate the material removal [12]; (b) water based chemical reaction between the FS and the polishing grains, the classical chemical 'bond bridge' effects proposed by Cook is well-acknowledged to explain the MRR enhancement [13].…”
Section: Introductionmentioning
confidence: 99%
“…5 Chemical mechanical polishing is considered as the most effective global flattening technology. 6,7 However, it takes a lot of time to obtain ultra-smooth surface using a single method, 8 due to the high hardness and good chemical stability of GaN. To date, great efforts have been made to fabricate GaN with low Ra and high material removal rate.…”
mentioning
confidence: 99%